STRATEGI CHINA DALAM MENGUASAI PERDAGANGAN SMARTPHONE DI INDONESIA MELALUI MEREK OPPO PADA PERUSAHAAN OPPO ELECTRONIC CORP - Fatmawati, Amalia; Murdani, Andika Drajat; Madyar Dewi, Untari Narulita (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Abstract Globalization has an effect on the development of science and technology. Every country is actively involved in following developments in science and technology. The era of globalization brings everyone face to face with change. Indonesia is one of the countries affected by the flow of globalization. The progress of science and technology in Indonesia is certainly inseparable from the effects of globalization. This development is marked by the increasing development of science and technology. Mastery of technology is a prestige and an indicator of a country's progress, including the country's society. The aim of this research is to find out China's strategy in making its country a country capable of controlling the Oppo brand smartphone trade in Southeast Asia. The author uses international trade theory and globalization theory to carry out the analysis in this research. The type of research used is qualitative research with primary data sources and secondary data sources. Advances in science and technology and Indonesia's lack of ability to produce its own smartphones have allowed China to promote it to the wider public who need cheap but good quality smartphones. One of the reasons for providing cheap prices is of course because advertising costs are not as extravagant as other products. Keywords: China; Globalization; Indonesia; International trade